Teaching with confidence a guide to enhancing teacher self-esteem - Lawrence, Denis (London : Paul Chapman, 1999)
The author focuses on the relationship between stress and self esteem, and sets out a programme of easy-to-use strategies to reduce them. He considers the increasing demands on teachers and personality characteristics in assessing ways to manage stress.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Teachers -- Job stress; Stress management; Self-esteem.; Teachers. -- Job stress